2009
DOI: 10.1152/jn.90735.2008
|View full text |Cite
|
Sign up to set email alerts
|

Head-Unrestrained Gaze Adaptation in the Rhesus Macaque

Abstract: . The ability to adjust the amplitude of gaze shifts in response to persistent visual errors ("gaze adaptation") has been investigated primarily by introducing visual errors at the end of saccades produced by head-restrained primates. Very little is known about the behavior and neural mechanisms underlying gaze adaptation when the head is free to move. We tested alternative hypotheses about the signals that are altered during gaze adaptation by increasing (25°3 50°; "forward adaptation") or decreasing (50°3 25… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 58 publications
0
11
0
Order By: Relevance
“…The locus of saccadic adaptation has been investigated with single-unit recording, stimulation, and lesion approaches. It has been demonstrated that saccadic adaptation occurs at a point where the saccade is represented as a vector (Hopp and Fuchs 2006) and affects gaze before it is separated into its eye and head components (Cecala and Freedman 2009;Phillips et al 1997). Neurons in the superior colliculus, even neurons that do not have visual responses, represent target location and not saccade amplitude in both the head-fixed (Frens and Van Opstal 1997;Quessy et al 2010) and unrestrained (DeSouza et al 2011;Fernandez-Ruiz et al 2007) conditions.…”
Section: Discussionmentioning
confidence: 99%
“…The locus of saccadic adaptation has been investigated with single-unit recording, stimulation, and lesion approaches. It has been demonstrated that saccadic adaptation occurs at a point where the saccade is represented as a vector (Hopp and Fuchs 2006) and affects gaze before it is separated into its eye and head components (Cecala and Freedman 2009;Phillips et al 1997). Neurons in the superior colliculus, even neurons that do not have visual responses, represent target location and not saccade amplitude in both the head-fixed (Frens and Van Opstal 1997;Quessy et al 2010) and unrestrained (DeSouza et al 2011;Fernandez-Ruiz et al 2007) conditions.…”
Section: Discussionmentioning
confidence: 99%
“…It has been frequently observed that forward adaptation takes longer to develop and reaches a lower level than backward adaptation, in both humans (Ethier et al, 2008a;Hernandez et al, 2008;Miller et al, 1981;Panouilleres et al, 2009c;Straube and Deubel, 1995) and monkeys (Cecala and Freedman, 2009;Straube et al, 1997). The difficulty to elicit adaptive saccade lengthening is particularly illustrated by Panouilleres et al (2009c) who reported that 5 out of 19 subjects tested in the forward condition did not demonstrate any significant adaptation after-effect, whereas all 14 subjects tested in the backward condition showed a significant adaptation after-effect.…”
Section: Amplitude Shortening Versus Lengthening (Backward Versus Formentioning
confidence: 99%
“…Adaptation of the amplitude of saccadic eye movements has often been investigated by introducing a visual error at the end of saccades (McLaughlin 1967; Miller et al 1981; Deubel et al 1986; Frens and van Opstal 1994; Frens and Opstal 1997; Phillips et al 1997; Straube et al 1997; Scudder et al 1998; Wallman and Fuchs 1998; Noto et al 1999; Hopp and Fuchs 2002; Robinson et al 2003; Alahyane and Pelisson 2004; Alahyane and Pelisson 2005; Takeichi et al 2005; Hopp and Fuchs 2006; Takeichi et al 2007; Cecala and Freedman 2008; Ethier et al 2008; Cecala and Freedman 2009). Over the course of repeated trials the amplitude of the initial saccade changes so that the error at the end of the primary saccade is reduced or increased depending on the direction of introduced visual error (McLaughlin 1967; Straube et al 1997; Noto et al 1999; Hopp and Fuchs 2004).…”
Section: Introductionmentioning
confidence: 99%